2017
DOI: 10.1080/08880018.2017.1323985
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss after platinum treatment is irreversible in noncranial irradiated childhood cancer survivors

Abstract: Cisplatin and carboplatin are effective antineoplastic agents. They are also considered to be potentially highly ototoxic. To date, no long-term follow-up data from well-documented cohorts with substantial numbers of childhood cancer survivors (CCS) with platinum-related hearing loss are available. Therefore, in this study, we studied the reversibility of ototoxicity from discontinuation of treatment onwards in a national cohort of platinum-treated survivors with hearing loss at the end of cancer treatment. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 22 publications
(38 reference statements)
1
59
0
Order By: Relevance
“…destructive effect on external auditory cells, which are not capable of regeneration (18). The means that the hearing loss after cisplatin-based treatment is irreversible (19). In this study, a patient with a mesenchymal-neuroectodermal tumor who had been treated with cisplatin was diagnosed with bilateral high-frequency hearing loss, which is consistent with literature reports (10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…destructive effect on external auditory cells, which are not capable of regeneration (18). The means that the hearing loss after cisplatin-based treatment is irreversible (19). In this study, a patient with a mesenchymal-neuroectodermal tumor who had been treated with cisplatin was diagnosed with bilateral high-frequency hearing loss, which is consistent with literature reports (10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 86%
“…Unfortunately, in our case no previous pure-tone audiometry tests were performed, which makes it impossible to determine whether the hearing loss is progressive or whether it has remained at the same level since the end of chemotherapy. In the literature, reports are stating that after the completion of treating hearing loss is permanent and stable (19,23). However, many authors have observed progressive hearing loss following chemotherapy with platinum compounds in children treated for solid tumors (15,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence regarding cardiac function on children prenatally exposed to anthracyclines is reassuring: non-clinically relevant differences in echocardiographic findings have been reported in exposed children compared with non-exposed ones [8,42,51,52]. Concerns related to hearing function throughout infancy are mainly based on data from young cancer survivors [53,54]. However, on indication, the use of carboplatinum during pregnancy is preferred, as there are case reports of impaired hearing in children prenatally exposed to cisplatin [8,41,55].…”
Section: Current Evidence On Outcome Of Children and Ongoing Researchmentioning
confidence: 99%
“…There is low quality evidence that hearing function in CAYA cancer survivors may deteriorate over time after treatment with platinum agents 34,35,[53][54][55][56] , head/brain radiotherapy, or a CSF shunt (level C evidence). 5,10,[57][58][59] However, in some survivors hearing function remains stable or even improves over time.…”
Section: Evidencementioning
confidence: 99%
“…5,10,[57][58][59] However, in some survivors hearing function remains stable or even improves over time. 34,35,[53][54][55][56]60 The predictors for change of hearing function over time are unknown. From existing literature, it is difficult to define an appropriate surveillance interval indicating the length of time during which testing should be performed.…”
Section: Evidencementioning
confidence: 99%